2022
DOI: 10.3324/haematol.2021.279981
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype and outcome associations in patients with Fanconi anemia: the National Cancer Institute cohort

Abstract: Fanconi anemia (FA) is caused by pathogenic variants in the FA/BRCA DNA repair pathway genes, and is characterized by congenital abnormalities, bone marrow failure (BMF) and increased cancer risk. We conducted a genotype-phenotype and outcomes study of 203 patients with FA in our cohort. We compared across the genes, FA/BRCA DNA repair pathways (upstream, ID complex and downstream), and type of pathogenic variants (hypomorphic or null). We explored differences between the patients evaluated in our clinic (clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…The spectrum of these type of anomalies includes hemivertebrae, hypoplastic vertebrae, vertebral fusion (Klippel-Feil syndrome), spina bifida, coccygeal aplasia, scoliosis, kyphosis, and atlantoaxial instability ( 37 , 133 , 260 ). A recent prospective study published that vertebrae anomalies are found in almost 50% of patients after intentional evaluation ( 245 ), which is in sharp contrast with the 4% described in the literature ( 37 , 133 ). Some reports have depicted less frequent anomalies, such as rib hypoplasia, Sprengel deformity, and hip dysplasia ( 149 , 225 , 261 264 ).…”
Section: Dysmorphological and Oncological Phenotype Of Patients With ...mentioning
confidence: 76%
See 1 more Smart Citation
“…The spectrum of these type of anomalies includes hemivertebrae, hypoplastic vertebrae, vertebral fusion (Klippel-Feil syndrome), spina bifida, coccygeal aplasia, scoliosis, kyphosis, and atlantoaxial instability ( 37 , 133 , 260 ). A recent prospective study published that vertebrae anomalies are found in almost 50% of patients after intentional evaluation ( 245 ), which is in sharp contrast with the 4% described in the literature ( 37 , 133 ). Some reports have depicted less frequent anomalies, such as rib hypoplasia, Sprengel deformity, and hip dysplasia ( 149 , 225 , 261 264 ).…”
Section: Dysmorphological and Oncological Phenotype Of Patients With ...mentioning
confidence: 76%
“…The most common alterations are pigmentary changes such as café-au-lait macules, generalized hyperpigmentation, and hypopigmented macules ( 37 , 133 ). Cross-sectional studies that intentionally looked for skin changes in patients with FA have found at least one pigmentary anomaly in 82–97% of evaluated patients ( 243 245 ). The most frequent finding was café-au-lait macules, with a mean of 7.5 per patient; they were distributed across the whole body ( 243 ).…”
Section: Dysmorphological and Oncological Phenotype Of Patients With ...mentioning
confidence: 99%
“…We combined data obtained from families seen at the NIH [Clinical Center (CC) cohort] with information from those for whom we had data who had not been seen at the NIH [the Field Cohort (FC)]. Further details about the cohort and analytic methods are provided in recent publications 8,12–14 …”
Section: Methodsmentioning
confidence: 99%
“…Further details about the cohort and analytic methods are provided in recent publications. 8,[12][13][14] We classified patients by the age at which FA was diagnosed as FA-PED (below age 18), and FA-ADULT (at or above age 18 years), with the additional complexity that each age group includes patients recognized as the index cases in the family, as well as others who were secondary cases within a family (Table 1). We included STs as an additional discriminant since that was the first sign in two FA-ADULT cases and was the eventual outcome for many of the FA-PED cases (Table 2).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation